Elements That Impact Building a Public Governance Model in Brazil: The Case of the Brazilian Navy - Érica Von Raschendorfer; Ariane Roder Figueira; Liliane Furtado (BBR: Brazilian Business Review)
This paper investigated the essential elements for building a public governance model in Brazil, with the objective of proposing an analytical framework with contributions from different theoretical lenses. The concepts and debates emerging from the literature were analyzed along with the normative instruments that guide the principles of public governance in Brazil, and, finally, empirical research was carried out in a Brazilian public organization (Brazilian Navy). The study found that, in the Brazilian context, external control bodies have been playing the role of giving rise to an increase in governance levels within the scope of public administration, restricting at first its application to the perspective of control, and involving, to a lesser extent, the concepts of governance as instruments for achieving political-administrative effectiveness. This result corroborates the need to develop more comprehensive proposals related to public value creation involving the structuring of both political and administrative bodies in Brazil.